REDESAIN ALAT KERJA BERBASIS ANTROPOMETRI ORANG BALI DAN REMODELING SIKAP KERJA MENURUNKAN POSTURAL STRES PRAMUGRAHA HOTEL PURI SARON SEMINYAK-KUTA BALI - Irwanti, NK Dewi (Akademi Komunitas MAPINDO, 2018)
Working with a trolley that is incompatible with anthropometry has risks in increasing postural stress, which manifests as fatigue and musculoskeletal complaints. This study aims to determine the room attendant fatigue and musculoskeletal complaints level when using a trolley; to find out the work posture score on activities using a trolley; to find out a trolley design which is compatible with Balinese anthropometry; to find out work posture score on the activity of using the trolley. This research was conducted experimentally using the same subject design (treatment by subject design). The number of samples was 14 employees. Two treatments were applied to the subjects, namely Period I or PI (the samples were working with the trolley) and Period II or PII (sample or room attendant Hotels working trolley according to Balinese anthropometry). Fatigue is measured using a questionnaire of 30 items of rating scale, musculoskeletal complaints using the Nordic body map. Measurement data were analyzed using descriptive and inferential analysis. Comparative analysis of the variables of fatigue, and muscle complaints using the Wilcoxon Test with a significance level of 5% (α = 0.05). The results showed that the mean fatigue and muscle complaints before and after work were significantly different where the value of p ​​​<0.05. Total RULA analysis score before treatment 6, after treatment 3. Work tool design is based on total ergonomic approach through TTG and SHIP approach. Keywords: Trolley, Anthropometry, Postural Stress, RULA Analysis